Peranan Guru dalam Mengembangkan Kecerdasan Emosional Siswa TK Al-Kautsar Kecamatan Mandau Kabupaten Bengkalis - Gusmayenti Gusmayenti; Suarni Norawati; Supardi Supardi (Dinasti Research, 2023)
The purpose of this research is to determine the role of teachers in developing students' emotional intelligence in Al-Kautsar Kindergarten, Mandau District, Bengkalis Regency. This research uses a descriptive qualitative method by collecting observation, interview and documentation data. The results of the research show that the role of teachers in building children's emotional intelligence at Al Kautsar Kindergarten can be concluded that the role of teachers in building children's emotional intelligence has been implemented well by teachers at school. This can be seen from children's play activities at school, children's behavior, and children's communication with other people, both teachers and friends. The teacher's role in building children's ability to recognize their own emotions is carried out through telling stories, role playing, guessing expressions, and approaching children by speaking directly. The teacher's role in building the ability to manage children's emotions is carried out through storytelling, habituation, role models and approaches to children. The teacher's role in building children's self-motivating abilities is carried out through providing encouragement/motivation, rewards, watching and training to children. The teacher's role in building children's empathetic abilities is carried out through habituation, direct practice, exemplary stories, and role playing. The teacher's role in building children's ability to build relationships with other people is carried out through group learning, project play, and direct practice. Factors that influence child development are parents, environmental factors, peers, school environment, physical changes, changes in interaction patterns with parents, changes in interactions with peers, changes in external views, and changes in interactions with school.